FAKTOR PENENTU KEBERHASILAN PROGRAM UKS PAUD DI PAUD WILAYAH DESA WEDOMARTANI SLEMAN YOGYAKARTA - ZENNI PUSPITARINI; LALA BUDI FITRIANA (CHMK NURSING SCIENTIFIC JOURNAL, 2018)
Background: At the age of 3 or 4 years, children who have started education in a preschool or early education (PAUD) environment spend more time at school than in a home environment. Schools play an important role in promoting healthy behavior and educating children to achieve maximum growth and development of children. Government programs related to health for schools are the School Health Unit (UKS) which aims to improve the quality of education and learning achievement of students by improving hygienic and healthy living behavior and improving the health status of students and school residents. In addition, the purpose of implementing UKS is to create a healthy environment, so as to enable optimal growth and development of children in the context of forming a full Indonesian human being. The study aims to identify the dominant factors that are the determinants of the success of the implementation of the UKS PAUD program in PAUD in the village of Wedomartani Sleman, Yogyakarta. Research Methods: Data collection was carried out in PAUD in the village of Wedomartani Sleman, Yogyakarta, with a sample of 32 teachers teaching in PAUD. This type of research is descriptive analytic with cross sectional method. The sampling technique uses simple random sampling. The research instrument is a questionnaire and a modified checklist sheet from various references. Bivariate data analysis using chi-square test. Multivariate analysis using logistic regression to test the interaction between variables to determine the interaction between independent variables on the dependent variable. Research Results: Most of the respondents held the position of Principal, namely 62%, late adult age, namely 41.4% and highly educated (D3, S1 and S2) at 72%. The results of the bivariate analysis of the relationship between knowledge, skills, infrastructure and perceptions of health personnel support, respectively with a p-value of 0.029; 0.010; 0,150; 0.014. Conclusion: There is a relationship between knowledge, skills and perceptions of health personnel support for the successful implementation of UKS PAUD in PAUD in the village of Wedomartani Sleman Yogyakarta Keywords: UKS, PAUD, preschool children